High-thermal-conductivity regenerated polyester fiber and preparation process thereof
By grafting the polyester segments on the surface of the nano-scale thermally conductive filler and melt-spinning using porous spinning plates, the problem of insufficient thermal conductivity of regenerated polyester fibers is solved, and the improvement of high thermal conductivity and mechanical properties is achieved.
Patent Information
- Application Number
- CN202411613615.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-02-18
AI Technical Summary
The thermal conductivity of existing recycled polyester fibers is insufficient, which affects its heat dissipation effect. At the same time, the particle size and dispersion of the thermally conductive filler are difficult to meet the high requirements of monofilament fibers.
By grafting the polyester segments on the surface of the nano-scale thermally conductive filler, the compatibility and dispersion of the thermally conductive filler and regenerated polyester are improved, and melt-spinned using porous spinning plates to enhance the thermal conductivity and mechanical properties of the fibers.
The thermal conductivity and mechanical properties of recycled polyester fibers are significantly improved, their heat dissipation properties are enhanced, and the melt viscosity increase caused by thermal fillers is avoided.
Smart Images

Figure BDA0005131561880000091
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of regenerated polyester fibers and relates to a high thermal conductivity regenerated polyester fiber and a preparation process thereof. Background Art
[0002] In the field of chemical fiber, monofilament refers to a chemical fiber filament with a diameter of 0.04-0.15mm. Depending on the different materials, it can be used in printing screens, cicada wing cloths, gap cloths, blackout cloths, glittering fabrics, wedding dresses, underwear, shoe materials, mattresses, integrated circuit printed boards and other fields. It has high added value, lucrative profits, and broad application prospects. The existing monofilament manufacturing process mainly adopts the mother fiber fiber splitting process. The melt is multi-hole spun through a multi-hole spinneret to first prepare a bundle of mother fibers. Then, the mother fibers are split into fibers using a fiber splitting device to obtain monofilaments, which are then used for processing in subsequent processes. However, the difficulty of the mother fiber fiber splitting process to obtain monofilaments is that the diameter of the mother fiber bundle is relatively thick and difficult to cool. If the mother fiber is not cooled in time, it will affect the performance of the monofilament and the processing of subsequent processes.
[0003] In order to improve the cooling effect of the mother yarn, the existing improvement of the mother yarn fiber separation process is mainly to increase the air cooling intensity at the outlet of the porous spinneret to increase the cooling speed. Summary of the invention
[0004] For recycled polyester mother yarn, improving the thermal conductivity of recycled polyester mother yarn can further improve its heat dissipation performance. The main method to improve the thermal conductivity of fiber is to add thermal conductive fillers, such as graphene, aluminum nitride, aluminum oxide, etc., but because the single fiber is very fine, very high requirements are placed on the particle size and dispersibility of the thermal conductive filler. Based on this, the present invention provides a high thermal conductivity recycled polyester fiber and a preparation method thereof.
[0005] The technical solution of the present invention is as follows:
[0006] A high thermal conductivity recycled polyester fiber, the raw material components of which include, by weight: 100 parts of recycled polyester and 5-30 parts of surface-modified nano-scale thermal conductive filler;
[0007] The preparation steps of the surface-modified nanoscale thermally conductive filler include:
[0008] The polyester diol and the diisocyanate compound are mixed in a molar ratio of 1:1.3-2 and reacted until the NCO content in the reaction system remains unchanged to obtain a prepolymer;
[0009] The amino-modified nano-scale thermal conductive filler is added to the prepolymer and the reaction is continued until the reaction is complete to obtain the product.
[0010] Preferably, the intrinsic viscosity of the recycled polyester is 0.50-0.85 dL / g.
[0011] Preferably, the nanoscale thermally conductive filler has an average particle size of 1-100 nm and is selected from one or a combination of two or more of aluminum oxide, aluminum nitride, boron nitride, silicon carbide, silicon nitride and silicon powder.
[0012] Preferably, the number average molecular weight of the polyester diol is 400-2000.
[0013] Preferably, the diisocyanate compound is selected from one or a combination of two or more of isophorone diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, 3,3'-dicyclohexylmethane diisocyanate, hexamethylene diisocyanate, 1,4-cyclohexane diisocyanate, methylcyclohexane diisocyanate, norbornane dimethylene isocyanate and L-lysine diisocyanate.
[0014] Preferably, the amino-modified nano-scale thermally conductive filler is prepared by modifying the nano-scale thermally conductive filler with an aminosilane coupling agent.
[0015] More preferably, the structure of the aminosilane coupling agent is as shown in the following formula (I):
[0016] R 1 NHR 2 Me x Si(OR 3 ) 3-x (Ⅰ)
[0017] Among them, R 1 is selected from H, C1-C4 alkyl, C5-C6 cycloalkyl or C6-C12 substituted cycloalkyl, R 2 is selected from C2-C6 alkylene or C3-C8 substituted alkylene, R 3 Selected from C1-C4 alkyl, Me represents methyl, and x=0-1.
[0018] Preferably, the weight ratio of the prepolymer to the amino-modified nanoscale thermally conductive filler is 1-5:1.
[0019] Preferably, the reaction temperature of the continued reaction does not exceed 60°C.
[0020] A process for preparing the high thermal conductivity regenerated polyester fiber according to any one of the above embodiments, comprising drying, spinning, cooling, oiling, and winding;
[0021] The spinning adopts a porous spinning plate.
[0022] The beneficial effects of the present invention are:
[0023] (1) The present invention bonds and grafts a polyester structure onto the surface of a nano-scale thermally conductive filler through the reaction of isocyanate and amino groups, and has good compatibility with recycled polyester, which can significantly improve the dispersibility of the thermally conductive filler in the recycled polyester, improve the thermal conductivity of the recycled polyester, and also improve some mechanical properties;
[0024] (2) The presence of polyester chain segments in the surface-modified nanoscale thermally conductive filler of the present invention plays a good plasticizing role during melt spinning of the recycled polyester, thereby preventing the melt viscosity from increasing during melt spinning and affecting the spinning effect. DETAILED DESCRIPTION
[0025] The technical solution of the present invention is further illustrated and described below through specific implementation methods.
[0026] In order to improve the dispersibility of the thermally conductive filler in the recycled polyester and avoid the increase of the melt viscosity of the recycled polyester during melt spinning and the influence of the spinning effect due to the addition of the thermally conductive filler, on the one hand, the present invention provides a high thermally conductive recycled polyester fiber, which comprises, by weight, 100 parts of recycled polyester and 5-30 parts of surface-modified nano-scale thermally conductive filler;
[0027] The preparation steps of the surface-modified nano-scale thermally conductive filler include:
[0028] The polyester diol and the diisocyanate compound are mixed in a molar ratio of 1:1.3-2 and reacted until the NCO content in the reaction system remains unchanged to obtain a prepolymer;
[0029] Amino-modified nano-scale thermal conductive filler is added to the prepolymer, and the reaction is continued until the reaction is complete to obtain the product.
[0030] The diameter of the recycled polyester monofilament is very low, and the thermal conductive filler added to improve thermal conductivity must be nano-scale. The agglomeration of nano-scale thermal conductive fillers is relatively serious. In order to improve the compatibility and dispersibility of nano-scale thermal conductive fillers with recycled polyester, the polyester chain segments are grafted on the surface of the nano-scale thermal conductive fillers in the present invention. The polyester chain segments have good compatibility with the recycled polyester, and because the molecular weight of the polyester chain segments is not low, the impact on the performance of the recycled polyester is relatively low. When the high thermal conductivity recycled polyester is melt-spun, the polyester chain segments can play a good plasticizing role, avoiding the problem of increased melt viscosity caused by the added nano-scale thermal conductive fillers.
[0031] In the present invention, in order to graft the polyester chain segment on the surface of the nano-scale thermal conductive filler, a method is adopted in which a polyester prepolymer is first prepared and then reacted with the nano-scale thermal conductive filler with an amino group through a reaction between an NCO group and an amino group. For the reaction of the polyester diol and the diisocyanate compound to prepare the prepolymer, the molar ratio of the polyester diol and the diisocyanate compound can be any value among 1:1.3, 1:1.4, 1:1.5, 1:1.6, 1:1.7, 1:1.8, 1:1.9, 1:2, etc. or any value in between, without any particular limitation.
[0032] In a preferred embodiment of the present invention, the intrinsic viscosity of the recycled polyester is 0.50-0.85 dL / g. The recycled polyester may contain some mechanical impurities, which affect the spinning effect and need to go through the steps of impurity removal, such as vibrating screen impurity removal and melt filter impurity removal. The intrinsic viscosity of the recycled polyester is closely related to its molecular weight, and the molecular weight has a great influence on the mechanical strength of the recycled polyester. Generally, the higher the intrinsic viscosity of the recycled polyester, the higher the molecular weight, and the higher the mechanical strength. Therefore, in order to make the obtained regenerated polyester fiber (mother yarn or filament) have better mechanical strength, the intrinsic viscosity of the recycled polyester can be 0.70-0.85 dL / g.
[0033] In a preferred embodiment of the present invention, the average particle size of the nano-scale thermal conductive filler is 1-100 nm, and can be selected from one or a combination of two or more of aluminum oxide, aluminum nitride, boron nitride, silicon carbide, silicon nitride and silicon micropowder. In addition to providing thermal conductivity, the nano-scale thermal conductive filler also has a certain reinforcing effect on the recycled polyester at an appropriate dosage, thereby improving the mechanical strength of the recycled polyester.
[0034] In a preferred embodiment of the present invention, the number average molecular weight of the polyester diol is 400-2000. If the molecular weight of the polyester diol is too large, it will affect the reactivity of the isocyanate group of the terminal group of the prepolymer obtained after the reaction with the diisocyanate. If the molecular weight of the polyester diol is insufficient, the effect is not obvious. In the present invention, the polyester diol is not particularly limited, and can be polycarbonate diol (PC-OH), polycaprolactone diol (PCL-OH), or a polyester diol obtained by condensation of adipic acid and 1,4-butanediol, etc.
[0035] In a preferred embodiment of the present invention, the diisocyanate compound is selected from aliphatic diisocyanates, and aliphatic diisocyanates have good weather resistance and good anti-yellowing performance. The aliphatic diisocyanate can be one or a combination of two or more of isophorone diisocyanate IPDI, 4,4'-dicyclohexylmethane diisocyanate HMDI, 3,3'-dicyclohexylmethane diisocyanate, hexamethylene diisocyanate HDI, 1,4-cyclohexane diisocyanate, methylcyclohexane diisocyanate, norbornane dimethylene isocyanate and L-lysine diisocyanate.
[0036] In a preferred embodiment of the present invention, the amino-modified nanoscale thermally conductive filler is modified by an aminosilane coupling agent. The amino-modified nanoscale thermally conductive filler is a nanoscale thermally conductive filler with an amino group chemically bonded on the surface of the nanoscale thermally conductive filler. The more commonly used method is through the reaction of an aminosilane coupling agent with a thermally conductive filler. Modification of nanoscale thermally conductive fillers with an aminosilane coupling agent is a routine operation in the field. A specific operation can be as follows: add the nanoscale thermally conductive filler to an organic solvent (such as anhydrous ethanol, methanol), ultrasonically disperse it, and then add an aminosilane coupling agent. The reaction is carried out at room temperature or not more than 60°C for 1-5 hours, and the solid is collected, washed, and dried.
[0037] In a more preferred embodiment of the present invention, the structure of the aminosilane coupling agent is shown in the following formula (I), R 1 NHR 2 Me x Si(OR 3 ) 3-x (Ⅰ)
[0038] Among them, R 1 is selected from H, C1-C4 alkyl, C5-C6 cycloalkyl or C6-C12 substituted cycloalkyl, R 2 is selected from C2-C6 alkylene or C3-C8 substituted alkylene, R 3 Selected from C1-C4 alkyl, Me represents methyl, and x=0-1.
[0039] In the present invention, the amino group of the aminosilane coupling agent can be a primary amino group or a secondary amino group, without particular limitation. For example, the aminosilane coupling agent can be 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-aminopropylmethyldimethoxysilane, 3-aminopropylmethyldiethoxysilane, β-aminoethyl-γ-aminopropyltrimethoxysilane, β-aminoethyl-γ-aminopropyltriethoxysilane, cyclohexylaminopropyltrimethoxysilane, cyclohexylaminopropylmethyldimethoxysilane, cyclohexylaminopropyltriethoxysilane, N-methyl-3-aminopropyltrimethoxysilane, N-methyl-3-aminopropyltriethoxysilane, etc.
[0040] In a preferred embodiment of the present invention, the weight ratio of the prepolymer and the amino-modified nano-scale thermally conductive filler is 1-5:1. The amount of the nano-scale thermally conductive filler added to the recycled polyester should not be too high or too low. If it is too high, the mechanical properties of the recycled polyester will be significantly deteriorated, and if it is too low, the thermal conductivity effect will not be obvious. In the present invention, adjusting the ratio of the prepolymer and the amino-modified nano-scale thermally conductive filler is used as a method to adjust the amount of nano-scale thermally conductive filler added. For example, the weight ratio of the prepolymer and the amino-modified nano-scale thermally conductive filler can be any value of 1:1, 1.5:1, 2:1, 2.5:1, 3:1, 3.5:1, 4:1, 4.5:1, 5:1, etc. or any value in between, without special restrictions.
[0041] In a preferred embodiment of the present invention, the reaction temperature for the continued reaction does not exceed 60°C. In the reaction between the NCO group and the amino group of the prepolymer, if the reaction temperature is high, the reaction between NCO and the amino group is relatively complicated, which may lead to the generation of a cross-linking reaction, and the surface-modified nano-scale thermally conductive fillers form a cross-linked structure through polyester-polyurethane, which is not conducive to the subsequent dispersion of the nano-scale thermally conductive fillers in the recycled polyester. By controlling the reaction temperature of the NCO group and the amino group, the NCO group and the amino group can react, and the nano-scale thermally conductive filler reacts with the prepolymer, while avoiding the reaction being too complicated, resulting in problems such as cross-linking, which in turn affects the dispersion of the nano-scale thermally conductive filler in the recycled polyester.
[0042] On the other hand, the present invention also provides a preparation process of the high thermal conductivity regenerated polyester fiber described in any one of the above embodiments, comprising drying, melt spinning, cooling, oiling, and winding;
[0043] The spinning process uses a porous spinning plate. The mother yarn obtained by using a porous spinning plate is thicker, but has better thermal conductivity, which can achieve faster cooling in the cooling step, which is more conducive to the stability of the mother yarn performance. After fiber separation, single yarn can be obtained.
[0044] Specifically, drying can be performed by hot air drying at 120-180°C for 2-10 hours, and the criterion is that the moisture content of the recycled polyester is reduced to no more than 0.1wt%; melt spinning can be performed at around 280°C, with a spinning speed of 500-2000m / min; cooling can be performed by air cooling; and the oiling agent can be purchased directly from the market.
[0045] The technical solution of the present invention is further described and illustrated according to various embodiments below. Unless otherwise specified, the parts described in the following embodiments are parts by weight.
[0046] Preparation Example 1-4 Preparation of surface-modified nanoscale thermally conductive filler
[0047] Preparation Example 1
[0048] Polycarbonate diol (number average molecular weight 1000) and IPDI were added into a reaction container at a molar ratio of 1:1.5, stirred and mixed at room temperature and reacted until the content of NCO groups in the reaction system remained unchanged, to obtain a prepolymer;
[0049] Add 1 part of amino-modified nano-SiC to 1 part of the above prepolymer, stir at 1200 rpm for 10 min at room temperature, then lower the stirring speed to 500 rpm and react until the reaction is complete to obtain surface-modified nano-SiC.
[0050] Amino-modified nano-scale SiC was prepared as follows: 5 parts of SiC with an average particle size of 20 nm were added to 100 parts of anhydrous ethanol, ultrasonically dispersed for 10 min, 1 part of N-methyl-3-aminopropyltrimethoxysilane was added, and the reaction was stirred at room temperature for 3 hours. The solid was collected and washed twice with anhydrous ethanol, and dried in an oven at 50°C overnight to obtain amino-modified nano-scale SiC.
[0051] Preparation Example 2
[0052] The difference between this preparation example and preparation example 1 is that the prepolymer in preparation example 1 is adjusted from 1 part to 5 parts. The other steps remain unchanged.
[0053] Preparation Example 3
[0054] Add polycarbonate diol (number average molecular weight 800) and IPDI in a molar ratio of 1:1.3 into a reaction container, stir and mix at room temperature and react until the content of NCO groups in the reaction system remains unchanged to obtain a prepolymer;
[0055] Add 1 part of amino-modified nano-alumina to 3 parts of the above prepolymer, stir at 1200 rpm for 10 min at room temperature, then lower the stirring speed to 450 rpm and react until the reaction is complete to obtain surface-modified nano-alumina.
[0056] Amino-modified nano-alumina was prepared as follows: 5 parts of alumina with an average particle size of 10 nm were added to 100 parts of anhydrous ethanol, ultrasonically dispersed for 10 minutes, 1 part of 3-aminopropyltrimethoxysilane was added, and the reaction was stirred at room temperature for 3 hours. The solid was collected and washed twice with anhydrous ethanol, and dried in an oven at 50°C overnight to obtain amino-modified nano-alumina.
[0057] Preparation Example 4
[0058] The difference between this preparation example and preparation example 3 is that the molar ratio of polycarbonate diol to IPDI in preparation example 3 is adjusted from 1:1.3 to 1:2. The other steps remain unchanged.
[0059] Example 1
[0060] The recycled polyester (characteristic viscosity 0.75 dL / g) was vibrated and melt filtered to remove impurities, then mixed with 100 parts of the recycled polyester and 5 parts of the surface-modified nano-SiC of Preparation Example 1, dried at 150°C for 8 hours, with a water content of less than 0.1wt%. The mixture was melt-spun through a porous spinning plate at 280°C at a spinning speed of 1500m / min, air-cooled, oiled, and wound to obtain a mother yarn, which was then fiberized to obtain a single yarn with an average diameter of 0.1mm.
[0061] Example 2
[0062] The difference between this embodiment and embodiment 1 is that in embodiment 1, the surface modified nano-SiC is adjusted from 5 parts to 12 parts. The other steps remain unchanged.
[0063] Example 3
[0064] The difference between this embodiment and embodiment 1 is that in embodiment 1, the surface modified nano-SiC is adjusted from 5 parts to 20 parts. The other steps remain unchanged.
[0065] Example 4
[0066] The difference between this embodiment and embodiment 1 is that in embodiment 1, the surface modified nano-SiC is adjusted from 5 parts to 30 parts. The other steps remain unchanged.
[0067] Example 5
[0068] The difference between this example and Example 4 is that in Example 4, the surface-modified nano-SiC in Preparation Example 1 is replaced by an equal weight of the surface-modified nano-SiC in Preparation Example 2. The remaining steps remain unchanged.
[0069] Comparative Example 1
[0070] The difference between this comparative example and Example 1 is that in Example 1, no surface-modified nano-SiC is added. The remaining steps remain unchanged.
[0071] Comparative Example 2
[0072] The difference between this comparative example and Example 1 is that in Example 1, the surface modified nano-SiC in Preparation Example 1 is replaced by an equal weight of unmodified nano-SiC in Preparation Example 1. The remaining steps remain unchanged.
[0073] Comparative Example 3
[0074] The difference between this comparative example and Example 1 is that in Example 1, the surface modified nano-SiC in Preparation Example 1 is replaced by an equal weight of methyl-modified nano-SiC. The remaining steps remain unchanged.
[0075] The methyl-modified nano-SiC was prepared as follows: 5 parts of SiC with an average particle size of 20 nm were added to 100 parts of anhydrous ethanol, ultrasonically dispersed for 10 min, 1 part of methyltrimethoxysilane was added, stirred and reacted at room temperature for 3 hours, the solid was collected and washed twice with anhydrous ethanol, and dried in an oven at 50°C overnight to obtain methyl-modified nano-SiC.
[0076] Example 6
[0077] The recycled polyester (characteristic viscosity 0.80 dL / g) was vibrated and melt filtered to remove impurities, then mixed with 100 parts of the recycled polyester and 15 parts of the surface-modified nano-alumina of Preparation Example 3, and dried at 140°C for 10 hours with a water content of less than 0.1wt%. The mixture was melt-spun through a porous spinning plate at 282°C with a spinning speed of 1600 m / min. After air cooling, the mixture was oiled and wound to obtain a mother yarn. The mother yarn was fiberized to obtain a single yarn with an average diameter of 0.08 mm.
[0078] Example 7
[0079] The difference between this example and Example 6 is that in Example 6, the surface-modified nano-alumina of Preparation Example 3 is replaced by an equal weight of the surface-modified nano-alumina of Preparation Example 4. The remaining steps remain unchanged.
[0080] Example 8
[0081] The difference between this example and Example 7 is that in Example 7, the surface-modified nano-alumina in Preparation Example 4 is adjusted from 15 parts to 25 parts. The remaining steps remain unchanged.
[0082] Performance Testing
[0083] Thermal conductivity: The monofilaments of Examples 1-8 and Comparative Examples 1-3 were woven into fabrics, and the thermal conductivity of the fabrics was tested using a Xiangke DRL-V thermal conductivity tester.
[0084] Tensile strength and elongation at break: tested according to the method of GB / T3916-2013.
[0085] Melt viscosity: measured at 280°C using a cone-plate viscometer with a shear rate of 10,000 s -1 .
[0086] The results are shown in Table 1 below.
[0087] Table 1
[0088]
[0089] It can be seen from the data results in Table 1 above that the high thermal conductivity recycled polyester fiber of the present invention has good thermal conductivity, and the addition amount of thermal conductive filler is within a certain range, which promotes the improvement of tensile strength, elongation at break and melt viscosity.
[0090] As described above, the basic principles, main features and advantages of the present invention are shown and described. Those skilled in the art should understand that the present invention is not limited by the above embodiments, which are only preferred embodiments of the present invention and cannot be used to limit the scope of the present invention. That is, equivalent changes and modifications made according to the scope of the present invention and the content of the specification should still be within the scope of the present invention. The scope of protection required by the present invention is defined by the attached claims and their equivalents.
Claims
1. A high thermal conductivity recycled polyester fiber, characterized in that: The raw material components include, by weight: 100 parts of recycled polyester and 5-30 parts of surface-modified nano-scale thermal conductive filler; The preparation steps of the surface-modified nanoscale thermally conductive filler include: The polyester diol and the diisocyanate compound are mixed in a molar ratio of 1:1.3-2 and reacted until the NCO content in the reaction system remains unchanged to obtain a prepolymer; The amino-modified nano-scale thermal conductive filler is added to the prepolymer and the reaction is continued until the reaction is complete to obtain the product.
2. The high thermal conductivity recycled polyester fiber according to claim 1, characterized in that: The intrinsic viscosity of the recycled polyester is 0.50-0.85 dL / g.
3. The high thermal conductivity recycled polyester fiber according to claim 1, characterized in that: The nanoscale thermal conductive filler has an average particle size of 1-100 nm and is selected from one or a combination of two or more of aluminum oxide, aluminum nitride, boron nitride, silicon carbide, silicon nitride and silicon micropowder.
4. The high thermal conductivity recycled polyester fiber according to claim 1, characterized in that: The number average molecular weight of the polyester diol is 400-2000.
5. The high thermal conductivity recycled polyester fiber according to claim 1, characterized in that: The diisocyanate compound is selected from one or a combination of two or more of isophorone diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, 3,3'-dicyclohexylmethane diisocyanate, hexamethylene diisocyanate, 1,4-cyclohexane diisocyanate, methylcyclohexane diisocyanate, norbornane dimethylene isocyanate and L-lysine diisocyanate.
6. The high thermal conductivity recycled polyester fiber according to claim 1, characterized in that: The amino-modified nano-scale thermally conductive filler is prepared by modifying the nano-scale thermally conductive filler with an aminosilane coupling agent.
7. The high thermal conductivity recycled polyester fiber according to claim 6, characterized in that: The structure of the aminosilane coupling agent is shown in the following formula (I): R 1 NHR 2 Along with x Si(OR 3 ) 3-x (Ⅰ) Among them, R 1 is selected from H, C1-C4 alkyl, C5-C6 cycloalkyl or C6-C12 substituted cycloalkyl, R 2 is selected from C2-C6 alkylene or C3-C8 substituted alkylene, R 3 Selected from C1-C4 alkyl, Me represents methyl, and x=0-1.
8. The high thermal conductivity recycled polyester fiber according to claim 1, characterized in that: The weight ratio of the prepolymer to the amino-modified nano-scale thermally conductive filler is 1-5:
1.
9. The high thermal conductivity recycled polyester fiber according to claim 1, characterized in that: The reaction temperature of the continued reaction does not exceed 60°C.
10. A process for preparing the high thermal conductivity recycled polyester fiber according to any one of claims 1 to 9, characterized in that: Including drying, spinning, cooling, oiling, and winding; The spinning adopts a porous spinning plate.